جريمة التحرش الجنسي بالأطفال في القانون السعودي - فضيلي، محمد علي (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2017)
The research aims to study the offense of child sexual abuse in Saudi Arabian Law. Descriptive analytical and applied deductive methods have been applied to achieve the objectives of the study. The findings indicate that the offense of sexual abuse is one of the biggest offences in Saudi Arabia. It also show that Islamic Law already addresses this kind of offence for more than fourteen centuries, as it is already considered it as an offence where it places some punishment to be applied in order to deter people from it. The findings also show that effort has been made by the international community to tackle this offence, and this could be clearly seen through many conventions signed by the international community especially in respect to the protection of children. In addition, the findings also indicate that there are legal shortcomings with regard to sexual abuse particularly those involving children. The study recommends that additional research should be conducted in relation to the sexual abuse of children. The study also recommends that the international community in general and the Saudi Arabian government in particular should issue a special law to address this offence.